Dobutamine Stress Echocardiography with B-Mode Speckle Tracking in Patients after Acute Coronary Syndromes: Diagnostic and Prognostic Value - Potashev, S. V.; Salo, S. V.; Gavrylyshyn, A. Y.; Rudenko, S. A.; Holtvian, O. M. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Speckle tracking echocardiography (STE) provides valuable data on myocardial function. STE during dobutamine stress echocardiography (DSE) allows reliable myocardial ischemia diagnosis. Aim. To evaluate STE during DSE in patients with coronary artery disease (CAD) after acute coronary syndrome (ACS) and its accuracy in ischemia diagnosis, assessment of myocardial viability and coronary reserve. Methods. We examined 58 patients (55 [94,8 %] men and 3 [5,2 %] women) men) with CAD after ACS admitted to our Institute for defining indications for coronary interventions. All the patients underwent DSE with STE for longitudinal strain quantification. Results. Mean left ventricular ejection fraction (LVEF) was 52.4±5.8%. Significant CAD according to coronary angiography (CAG) prior to DSE was proved in 38 (65.5%) patients. All the patients had a history of ACS up to 12 years before the examination (38 [65.5%] patients after percutaneous coronary intervention (PCI), including 18 [31.0%] primary PCI; 9 [15.5%] patients after coronary artery bypass grafting (CABG); 3 [5.2%] after graft PCI, 1 [1.72%] patient after aortic valve replacement (AVR) with dilated cardiomyopathy (DCM) phenotype). There were no significant complications during DSE: 5 (8.6%) cases of relatively low grade transient arrhythmia with no need for intervention. As per DSE results, we performed 35 (60.3%) revascularization interventions: 31 (58.6%) PCI’s and 4 (6.9%) CABG procedures with good outcomes. It was shown that DSE with STE sensitivity and specificity were 89.7% and 94.7% (AUC 0.92), respectively, with positive and negative predictive values of 97.2% and 81.8%, respectively, with extremely high OR 157.5, p<0.0001. Combined quantification of ΔGLS and ΔWMSI showed insignificantly lower sensitivity (86.3% [p=0.57]) and specificity (87.8% [p=0.19]) vs. integral semiquantitative ischemia markers with significantly lower overall method accuracy (AUC 0.79, p=0.047). Conclusions. DSE with STE as a visualization method is a safe and optimal method for ischemia diagnosis, as well as for myocardial viability and coronary reserve assessment in patients with CAD after ACS with the aim of risk stratification and defining indications for interventions and myocardial revascularization.